2022
DOI: 10.3389/fbioe.2022.978917
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison between unilateral and bilateral percutaneous vertebroplasty for osteoporotic vertebral compression fractures: A finite element analysis

Abstract: Background and objective: The osteoporotic vertebral compression fracture (OVCF) has an incidence of 7.8/1000 person-years at 55–65 years. At 75 years or older, the incidence increases to 19.6/1000 person-years in females and 5.2–9.3/1000 person-years in males. To solve this problem, percutaneous vertebroplasty (PVP) was developed in recent years and has been widely used in clinical practice to treat OVCF. Are the clinical effects of unilateral percutaneous vertebroplasty (UPVP) and bilateral percutaneous vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…Low spinal stability may lead to an increased risk of recompression. In this study, filling with bone cement reduced the maximum displacement of the KD specimens and approached the intact vertebrae, which was also demonstrated by some related studies ( Dai et al, 2022 ). However, in the PKP group, the specimens still differed from the intact vertebrae in terms of stability during rotation.…”
Section: Discussionsupporting
confidence: 87%
“…Low spinal stability may lead to an increased risk of recompression. In this study, filling with bone cement reduced the maximum displacement of the KD specimens and approached the intact vertebrae, which was also demonstrated by some related studies ( Dai et al, 2022 ). However, in the PKP group, the specimens still differed from the intact vertebrae in terms of stability during rotation.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies have shown that cement distribution and vertebral stiffness are important factors affecting the stress balance of the vertebral body for recompression fractures of the vertebral body after PVP [33]. This asymmetric cement distribution may reduce the stiffness of the non-reinforcing side, leading to fracture recurrence [34]. Therefore, PKP combined with hollow pedicle screws is superior to PKP combined with pediculoplasty and superior to PKP alone in reducing the risk of adjacent vertebral fracture, adjacent disc degeneration, and vertebral refracture, and bilateral surgery is superior to unilateral surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical imbalance can exacerbate the pressure load on the spine, leading to irreversible effects such as loss of height of the fractured vertebral body, disc degeneration in adjacent segments, and even vertebral fractures in adjacent segments [ 20 ]. A biomechanical study by Dai et al demonstrated that BPKP balanced vertebral stresses, reduced maximum disc stresses, and was more stable than UPKP [ 21 ]. Hou et al conducted a retrospective study and found that symmetrical distribution of bone cement in the vertebral body significantly reduced the incidence of vertebral recompression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%